2012
DOI: 10.7314/apjcp.2012.13.6.2913
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Women's Actions on Cervical Cancer Screening and Treatment in Karawang District, Indonesia

Abstract: Introduction: The impact of cervical cancer prevention programs depends on persuading women to go for screening and, if needed, treatment. As part of an evaluation of a pilot project in Indonesia, qualitative research was conducted to explore the factors that influence women's decisions regarding screening and treatment and to generate practical recommendations to increase service coverage and reduce loss to follow up. Methods: Research was conducted at 7 of the 17 public health centers in Karawang District th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(111 citation statements)
references
References 37 publications
5
92
0
14
Order By: Relevance
“…However, while there has been a steady increase in citations using quantitative methods since 2000, it is only in recent years (2010 onwards) that qualitative studies on NCDs have emerged. Of the 130 included citations, nine used qualitative research designs [52, 59, 74, 77, 88, 92, 93, 100, 117], two utilized mixed methodologies [47, 113], and seven focused on the project design or evaluation of risk factor interventions or NCD prevention [30, 51, 57, 61, 65, 78, 86]. Ten of the citations were based on gray reports [134–143].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while there has been a steady increase in citations using quantitative methods since 2000, it is only in recent years (2010 onwards) that qualitative studies on NCDs have emerged. Of the 130 included citations, nine used qualitative research designs [52, 59, 74, 77, 88, 92, 93, 100, 117], two utilized mixed methodologies [47, 113], and seven focused on the project design or evaluation of risk factor interventions or NCD prevention [30, 51, 57, 61, 65, 78, 86]. Ten of the citations were based on gray reports [134–143].…”
Section: Resultsmentioning
confidence: 99%
“…Through our review we identified 27 citations that dealt with NCD management at the structural policy level [25, 61, 88], clinical level [23, 54, 63, 72, 75, 83, 9092, 95, 106, 108, 110, 113], community [16, 38, 52, 73, 74, 100], family [105, 107], and individual level [59, 77]. At the structural level, we recognized three issues: health insurance services for NCD patients [88], the need for a better collaboration between health and registration sectors [61], and the need to address the double burden of NCDs and infectious diseases such as tuberculosis and diabetes [25], which might be aggravated by smoking [39].…”
Section: Resultsmentioning
confidence: 99%
“…The articles examined (27)(28)(45)(46)(47) show the need for proper organization of health services to increase the participation of women in cervical cancer screening programs.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions such as reminders and reductions in health service barriers are recommended to develop implementation guidelines on the increase in cervical cancer screening (45) . According to a qualitative survey carried out in Indonesia, dissemination of information about prevention, use of home visits by community health agents, and structural changes in health systems such as offering free exams are efficient interventions to increase women's adherence to cervical cancer prevention (46) . Another systematic review study to evaluate interventions oriented toward increased cervical cancer screening found that reminders and incentives to women, use of communication means, individual education in health, and reduction of structural barriers in health services are options that enable increasing adherence to prevention (47) .…”
Section: Multiple Interventionsmentioning
confidence: 99%
“…However, women who have been screened multiple times are at substantially lower risk than those only screened a few times suggesting that the quality of the screening could be improved[113]. An alternative for low-middle income countries is visual inspection with acetic acid and in a large project involving 45 000 women in Indonesia, 83.1% of visual inspection acetic acid-positive women sought cryotherapy[114]. Recent interest has focused on two HPV DNA tests-care HPV and Hybrid Capture 2[115] and detection of 14 high-risk HPVs with HPV 16 and HPV 18 genotyping by polymerase chain reaction[116].…”
Section: Cancer Screeningmentioning
confidence: 99%